The use of games as an effective method of learning a foreign language - Altynay, P.; Altynbek, М.; Shynybek, Z. (My University, 2016)
The problem of human motivation when learning a foreign language. It's - motivation, which awakens purposeful activity. In other words, the motivation - a system of factors determine human behavior. Currently, most new theme is awakening: the motivation of teachers today.
Keywords: motivation of a teacher; intrinsic and extrinsic motivation; career ladder; lifelong teaching